Event-based aperiodically intermittent pinning synchronization control strategy for linearly coupled complex networks. (May 2020) - He, Chao; Li, Junmin
Abstract: In this paper, a kind of event-based aperiodically intermittent pinning synchronization control strategies for linearly coupled complex networks over the directed topology is proposed. With the prescribed convergence performance dynamic, an event-triggered mechanism is presented to guarantee the globally exponential synchronization of the complex networks. Furthermore, a global and robust event-based mechanism is derived by some approximation techniques to handle with the measurement noises of the states and the exponential synchronization is achieved. Simultaneously, with the limitation of information transmission over the networks, through constructing a nonlinear filter dynamic, a robust event-triggered mechanism which is only dependent on the states of the pinned nodes is presented to asymptotically synchronize the complex networks. Moreover, to eliminate the conservation of the constant feedback gains, a synthetic design of the adaptive feedback law and event-triggered mechanism is proposed. It is proved that the asymptotical synchronization of the complex network and the boundedness of the adaptive feedback gains are guaranteed. With rigorous analysis, for all of the presented event-based mechanisms, the Zeno phenomenon is excluded. Finally, a numerical example is performed over the directed scale-free network to demonstrate the effectiveness of the algorithms.